Molten salt synthesis of MAX phases in the Ti-Al-C system. Issue 14 (November 2018) - Galvin, T.; Hyatt, N.C.; Rainforth, W.M.; Reaney, I.M.; Shepherd, D.
Abstract: The molten salt method was used to synthesise the MAX phase compounds Ti2 AlC and Ti3 AlC2 from elemental powders. Between 900–1000 °C, Ti2 AlC was formed alongside ancillary phases TiC and TiAl, which decreased in abundance with increasing synthesis temperature. Changing the stoichiometry and increasing the synthesis temperature to 1300 °C resulted in formation of Ti3 AlC2 alongside Ti2 AlC and TiC. The type of salt flux used had little effect on the product formation. The reaction pathway for Ti2 AlC was determined to be the initial formation of TiC1-x templating on the graphite and titanium aluminides.